Climate mitigation and adaptation is cancer prevention and control - Caitlin Rublee; Jean Bikomeye; Sheetal Rao; Marium Husain; Kirsten Beyer (Elsevier, 2023)
Climate change contributes to adverse outcomes and disruptions in cancer care with disproportionate impacts on specific populations. As the health effects of fossil fuel air pollution and planetary warming increase, transdisciplinary stakeholders across communities will be crucial to developing and implementing climate solutions as health solutions for patients affected by cancer. We provide a narrative review of four key themes at the intersection of climate change and cancer then describe potential opportunities to engage health care and community organizations, government agencies, public health entities, and clinicians dedicated to ensuring high quality cancer care for all. Through the review, we highlight that an expansion of climate-focused research funding and educational offerings for health professionals provides the foundation for ongoing action that can reduce health disparities, care disruptions, and health service demands while diminishing the carbon footprint of cancer care and improving patient-centered health outcomes. Lastly, we discuss lessons from the past that emphasize the importance of preparedness and swift action through scalable institutional, national, and international policies rooted in health, equity, and justice. We posit that through systematic and deliberate choice by those with decision making capabilities, climate mitigation and adaptation becomes cancer prevention and control.